TEARS OF THE SICK - FOLLOWERS OF IBN SINA (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article examines the medical services of Ibn Sina, also known as Avicenna, whose medical innovations left a lasting legacy in Islam's golden age. It explores his holistic approach to health and emphasizes the importance of diet, lifestyle and mental wellbeing. The study highlights Ibn Sina's pioneering work in the field of pharmacology, detailing his careful documentation of medicinal plants and compounds, his advances in surgical techniques, particularly his use of anesthetics. Additionally, his pioneering approach to mental health, clinical trials and evidence-based medicine will be explored. The influence of his students such as Abu Ubayd al-Juzhani on the preservation and expansion of his teachings is discussed and the transfer of knowledge during this time is shown. Ibn Sina's comprehensive model of medical education and his principles of public health and hygiene are also examined, revealing his holistic and empirical approach to medicine. This study highlights the lasting impact of Ibn Sina's contributions, which continue to inspire modern medical research and practice.